Watershed restoration and protection in the Bais Bay Basin, Philippines. - Walters, Bradley B.; Cadelina, Angelita .M.; Cardano, Ariston; Visitacion, Eduardo (UP Los Banos Institute of Environmental Science and Management, 1994)
ERMP reports, 12
Keywords: Watershed management--Philippines--Bais Bay Basin; Watershed management--citizen participation